2016
DOI: 10.1097/inf.0000000000001135
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severity of Chikungunya in Children

Abstract: Chikungunya appeared during the second half of 2014 in Colombia. A prospective cohort study was carried to detect differences and severity between neonates and older children. Of 54 children with chikungunya, neonates had a higher viral load and greater frequency of severe laboratory and clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
3
12
1
1
Order By: Relevance
“…As in this patient, elevated white cell counts have previously been noted in case reports of patients with severe CHIKV disease [ 32 35 ]. A recent study by Rolle et al [ 36 ] to assess predictive factors for severe forms of CHIKV disease found higher leukocyte counts in patients with severe disease.…”
Section: Discussionsupporting
confidence: 74%
“…As in this patient, elevated white cell counts have previously been noted in case reports of patients with severe CHIKV disease [ 32 35 ]. A recent study by Rolle et al [ 36 ] to assess predictive factors for severe forms of CHIKV disease found higher leukocyte counts in patients with severe disease.…”
Section: Discussionsupporting
confidence: 74%
“…Some of the results of this study have been published recently. 16 Recent estimates, also from Colombia, suggest a high economic impact of pediatric infection in this region. Indeed, the average cost per uncomplicated CHIKF case was US$ 517.5 for children !1 year of age and US$ 375.1 for children <1 year old.…”
Section: Discussionmentioning
confidence: 99%
“…Infants (<1 year old) with chikungunya are often hospitalized and admitted to an intensive care unit (ICU) 16,50 . The disease usually presents as fever and rash 51,52 ; arthralgia is difficult to assess in infants, but is perhaps expressed as irritability and excessive crying 28,50 . Skin rashes are common (~60-80%) and generalized, and include maculopapular rash, pigment changes, vesiculobullous lesions (fluidfilled lesions) and (sometimes extensive) desquamation (skin peeling) 16,[50][51][52] .…”
Section: Disease In Infants and Childrenmentioning
confidence: 99%
“…The disease usually presents as fever and rash 51,52 ; arthralgia is difficult to assess in infants, but is perhaps expressed as irritability and excessive crying 28,50 . Skin rashes are common (~60-80%) and generalized, and include maculopapular rash, pigment changes, vesiculobullous lesions (fluidfilled lesions) and (sometimes extensive) desquamation (skin peeling) 16,[50][51][52] . Atypical symptoms include (sometimes complex) seizures, diarrhoea, tachycardia, viral sepsis and septic shock [51][52][53][54] .…”
Section: Disease In Infants and Childrenmentioning
confidence: 99%